2015
DOI: 10.1038/srep07971
|View full text |Cite
|
Sign up to set email alerts
|

Fossils reject climate change as the cause of extinction of Caribbean bats

Abstract: We combined novel radiocarbon dates of bat fossils with time-scaled ecological niche models (ENM) to study bat extinctions in the Caribbean. Radiocarbon-dated fossils show that late Quaternary losses of bat populations took place during the late Holocene (<4 ka) rather than late Pleistocene (>10 ka). All bat radiocarbon dates from Abaco (Bahamas) that represent extirpated populations are younger than 4 ka. We include data on six bat species, three of which are Caribbean endemics, and include nectarivores as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 66 publications
3
57
1
1
Order By: Relevance
“…These may have included sloths during the Archaic, whose extinctions seem independent of climatic changes, but not human arrival (Steadman et al 2005). Other signs of human impacts involved the extinction or extirpation of reptile, mammal and bird species (Soto-Centeno & Steadman 2015;. Several Ceramic Age archaeological assemblages show an early emphasis on, and then major decline of, rice rats (family: Cricetidae) and land crabs, with a commensurate increase in mollusc species (Newsom & Wing 2004: 100, 102-104), suggesting overexploitation of terrestrial fauna and a move towards heavier reliance on marine foods.…”
Section: Caribbean Islands In Fluxmentioning
confidence: 99%
“…These may have included sloths during the Archaic, whose extinctions seem independent of climatic changes, but not human arrival (Steadman et al 2005). Other signs of human impacts involved the extinction or extirpation of reptile, mammal and bird species (Soto-Centeno & Steadman 2015;. Several Ceramic Age archaeological assemblages show an early emphasis on, and then major decline of, rice rats (family: Cricetidae) and land crabs, with a commensurate increase in mollusc species (Newsom & Wing 2004: 100, 102-104), suggesting overexploitation of terrestrial fauna and a move towards heavier reliance on marine foods.…”
Section: Caribbean Islands In Fluxmentioning
confidence: 99%
“…Changes in island area due to rising sea level and concomitant changes in cave availability due to flooding and loss of roosting habitats after the PHT have been proposed to explain Caribbean bat extinctions (Morgan, 2001;Dávalos and Russell, 2012). However, recent evidence from radiocarbon chronology has indicated that many bat fossils in the Caribbean are younger than previously thought, and that many species of bat survived the PHT by 5-7 ky (Soto-Centeno and Steadman, 2015). Furthermore, evidence from time-scaled ecological niche models (ENM) covering the LGM to the present have revealed that climate-based distributions for the bats Monophyllus redmani, Macrotus waterhousii, and Pteronotus parnellii remained largely stable over time (Soto-Centeno and Steadman, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…However, recent evidence from radiocarbon chronology has indicated that many bat fossils in the Caribbean are younger than previously thought, and that many species of bat survived the PHT by 5-7 ky (Soto-Centeno and Steadman, 2015). Furthermore, evidence from time-scaled ecological niche models (ENM) covering the LGM to the present have revealed that climate-based distributions for the bats Monophyllus redmani, Macrotus waterhousii, and Pteronotus parnellii remained largely stable over time (Soto-Centeno and Steadman, 2015). This evidence from fossils and ENMs suggests that some species of bats were able to maintain viable populations until the late Holocene despite habitat loss due to rising sea level after the PHT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This area is also known for its eventful history of human colonization, which is responsible for several extinctions during the past centuries (Brace et al, 2015;Kemp and Hadly, 2015;Soto-Centeno and Steadman, 2015;Steadman et al, 2015). On account of these phenomena, investigating the history of many regional taxa is a complex task.…”
Section: Introductionmentioning
confidence: 99%